The development of metastatic meningioma in a canine patient post-immunotherapy case report - Paine, Mercy; Chamberlin, Tamara; Buczek, Jennifer; McDonnell, Jay; White, Mary (Frontiers in Veterinary Science, 2026)
Metastatic meningioma is a rare occurrence in canine patients, with only four previous cases reported. This case report examines a recurrent meningioma with pulmonary metastasis in a male Labradoodle that survived 28 months post clinical presentation. The meningioma recurred following surgery and treatment with an autologous tumor cell lysate vaccine. This case explores the potential role of immunotherapy, by extending survival time, creating conditions that allow for the rare development of metastatic disease.